Unequal worlds : discrimination and social inequality in modern India - Verma, Vidhu, 1961- (New Delhi, India : Oxford University Press, 2015)
Contributes articles.
Includes bibliographical references and index.
Keywords: Equality -- India; Social justice -- India; Discrimination -- India